O trabalho das crianças na agricultura familiar capixaba - Siqueira, Marcia Smarzaro (2006)
This research analyzes the work on the routine of children in the capixaba agriculture family, especially the one which is developed on the coffee plantation, which, as it is known, absorbs the biggest number of rural workers in the state of Espírito Santo, including the work of children. A conceptual discussion about the work and childhood category is generated, situating them in the field of the new childhood sociology. It is presented a study about the social-economical and historical-cultural formation from the emergency of the agricultural and fundiary structure in the capixaba society. It is presented a chart of the representativity of the children's work in Espírito Santo from the decade of 1990 and it analyses the work of children in the familiar unit according to the following aspects: the contribution of the children at work; the intensity of the children' s work contribution; the levels of participation at work according to age and gender; work, school and time to play. The results put into evidence the relavant contribution of the children at the activity that is developed in the small family properties, particularlly those which produce coffee in Espírito Santo, as from official estatistic data and the analysis made based on interviews performed with subjects who were object of field research: children, parents, other members of the family and teachers